A novel Microcystis aeruginosa supported manganese catalyst for hydrogen generation through methanolysis of sodium borohydride. (28th April 2020) - Duman, Fatih; Atelge, M.R.; Kaya, Mustafa; Atabani, A.E.; Kumar, Gopalakrishnan; Sahin, U.; Unalan, S.
Abstract: In this study, Microcystis Aeruginosa (MA)- microalgae species was used for the first time as a support material with metal ions loading to fabricate a highly efficient catalyst for the hydrogen generation through methanolysis of sodium borohydride (NaBH4 ). Microalgae was pre-treated with hydrochloric acid (3 M HCl) for 24 h at 80 °C. Subsequently, different metal ions (Mn, Co, and Mo) were loaded to the pre-treated samples. Finally, metal-loaded samples were subjected to burning in oven to fabricate the catalyst. Primarily, manganese metal was selected based on the best metal performance. Afterwards, different metal loading ratios, burning temperatures and burning times were evaluated to synthesize the optimal MA-HCl-Mn catalyst. Results showed the optimal conditions as Mn ratio, burning temperature and time as 50%, 500 °C and 45 min, respectively. To characterize the catalyst, FTIR, SEM-EDX, XRD, XPS and TEM analyses were performed. Hydrogen generation via methanolysis was performed at various NaBH4 ratio of 1–7.5% while changing concentrations from 0.05 to 0.25 g catalysts with diverge temperatures of (30, 40, 50 and 60 °C). The maximum hydrogen generation rate (HGR) by this novel catalyst was found as 4335.3, 5949.9, 7649.4 and 8758.9 mLmin −1 gcat −1, respectively. Furthermore, the activation energy was determined to be 8.46 kJ mol −1 . Graphical abstract: Image 1 Highlights: Microcystis aeruginosa (microalga) was used as a support material for the first time. The maximum hydrogen production rate was found to be 8758.9 mLmin -1 gcat -1 at 60 °C. The activation energy was found to be 8.46 kJ mol -1 .